Performance of zero water discharge (ZWD) system with nitrifying bacteria Bacillus megaterium and microalgae Chaetoceros calcitrans components in super intensive pacific white shrimp Litopenaeus vannamei culture at low salinity - Rahim Rahim; Gede Suantika; Harish Muhammad (Jurnal Akuakultur Indonesia)
ABSTRACT This research aimed to obtain the performance of super intensive white shrimp rearing using zero water discharge (ZWD) system. This study consisted of four steps, (1) activation and cultivation of nitrifying bacteria, microalgae C. calcitrans and B. megaterium; (2) acclimatization of Pacific white shrimp PL10 with 30 g/L of salinity and decreasing salinity at 2–3 g/L/day; (3) conditioning of ZWD system; (4) white shrimp rearing in 400 L of tank for ten weeks. The experiment used three treatments, (a) shrimp reared without any addition of microbial agent with water exchange conducted every week as much as10–20% of total rearing volume as control (K); (b) ZWD systems with the applications of nitrifying bacteria, (C. calcitrans and B. megaterium) without water discharge  (P1); and (c) ZWD system with the application of microalgae C. calcitrans and B. megaterum without water discharge (P2). According to the results, application of nitrifying bacteria, microalgae C. calcitrans and B. megaterium were able to improve the performance of ZWD system performance of white shrimp rearing at low salinity. In addition, the ZWD system was also able to increase the growth rate and survival rate of shrimp when it compared to control. The best rearing performance was found in ZWD system with application of microalgae C. calcitrans and B. megaterium.